Circular Business Model Strategy of SMM Fashion Brand: The Impact Towards SDG Goals - Azzahra, Fatimah; Keliat, Cyntia (Syntax Corporation, 2024)
The linear system known as “Take-Make-Waste'' has positioned fashion and textile industry as the second largest waste contributor in the world after the oil and gas industry. Consequently, the disruptions we currently face have led us to the global textile waste crisis era, including Indonesia. On the other side, Ellen MacArthur Foundation observes an increase in market and business opportunities within the slow/circular fashion industry. This research aims to explore the business strategies of the Indonesian fashion brand, SMM, which has been committed to implementing responsible fashion practices since 2014 and actively addressing environmental impacts. Through value hill analysis as the research framework to identify current circular activities, gaps, and challenges faced by SMM, the analysis focuses on three stages: uphill, tophill, and downhill. This qualitative research employs semi-structured interview techniques, primary and secondary data observation to comprehensively understand the adopted circular business model. The research findings indicate that SMM utilizes Circular Supply Models as its primary business model, Resource & Recovery Models as an effort towards using 100% new materials, and Product Life Extension Models as a form of loyalty to its customers. These circular business model strategies have helped SMM reduce carbon emissions by nearly 20% of the total emitted. This indicates that SMM is a manufacturer promoting responsible consumption and production.